Advances in electromagnetic shielding properties of composite foams. Issue 14 (26th March 2021) - Zhao, Biao; Hamidinejad, Mahdi; Wang, Shuai; Bai, Pengwei; Che, Renchao; Zhang, Rui; Park, Chul B.
Abstract : In recent decades, problems with electromagnetic interference (EMI) radiation problems have arisen, that can seriously reduce the performance of precision devices nearby and threaten human health. Abstract : In recent decades, problems with electromagnetic interference (EMI) radiation problems have arisen, that can seriously reduce the performance of precision devices nearby and threaten human health. In consequence, it is important to seek high efficiency materials to suppress EMI pollution. Generally, high magnetic permeability or electrical conductivity is essential for efficient EMI shielding. Conventionally, various forms of metal construction (sheet/films, coatings, etc. ) are used for EMI shielding. However, metallic shielding has drawbacks that include high density, lack of corrosion resistance and expensive processing, which restrict its use in the modern electronic world. By contrast, conductive polymer composites (CPCs), formed from insulative polymers and conductive fillers, have attracted more and more interest from both industry and academia. CPCs have properties that offer great potential for application in efficient EMI shielding. These include low density, high flexibility, good chemical stability and easy processing and forming. From a theoretical viewpoint, it is generally accepted that the shielding of EM waves is due to the three basic mechanisms of reflection, absorption and multiple internal reflections. However, it must be recognized that the SE of CPCs has a close relation to the reflection mechanism, which can cause secondary EMI pollution. Therefore, materials with charge carriers or magnetic/electric dipoles as well as cellular structure should be the focus for the development of EMI shielding materials with strong absorption properties. On that basis, the main aim of this paper is to review the current position in research of the design of inorganic based foams (metal, carbon or MXene) and polymer composite foams as EMI shielding materials. On the one hand, these composite foams have the merit of being lightweight, and on the other hand, the special porous structure can effectively harvest microwaves by prolonging the travel path. As a result, absorption dominates EMI shielding, which satisfies current requirements of EMI shielding applications. This review also points out the future challenges and gives guidelines for finding solutions for the next generation of shielding applications using composite foams.